Role of TIM-3 in ovarian cancer: the forsaken cop or a new noble - Chang, Xiangyu; Miao, Jinwei (Frontiers in Immunology, 2024)
T cell immunoglobulin and mucin domain-3 (TIM-3), a crucial immune checkpoint following PD1 and CTLA4, is widely found in several immune cells. Nonetheless, its performance in recent clinical trials appears disappointing. Ovarian cancer (OC), a malignant tumor with a high mortality rate in gynecology, faces significant hurdles in immunotherapy. The broad presence of TIM-3 offers a new opportunity for immunotherapy in OC. This study reviews the role of TIM-3 in OC and assesses its potential as a target for immunotherapy. The regulatory effects of TIM-3 on the immune microenvironment in OC are discussed, with a focus on preclinical studies that demonstrate TIM-3's modulation of various immune cells in OC. Additionally, the potential therapeutic advantages and challenges of targeting TIM-3 in OC are examined.